Observation The Impacts of Various Type of Additive Materials on Concrete (A review) - Reem Hatem Ahmed; Aiham Nafea Yaseen Alkubaisi (Zien Journals, 2021)
The evolution of chemical admixtures for Portland cement concrete has seen significant success in recent decades. The majority of efforts have focused on enhancing the qualities of concrete with minimum expenditures via ready-mix providers & contractors in the form of specialized equipment, unique skills, & labor force education. This technique has resulted in building cost savings & widely acknowledged ready-made solutions for unanticipated construction challenges. The behavior of concrete that has been enhanced using superplasticizer additions is being investigated
Keywords: Admixtures; Chemical Admixtures; Mineral Admixtures